432 ACS-STEMI in a young man with triple positive antiphospholipid syndrome: clinical implications about antithrombotic therapy management. (8th December 2021) - Prandi, Francesca Romana; Milite, Marialucia; Celotto, Roberto; Lecis, Dalgisio; Marchei, Massimo; Romeo, Francesco; Barillà, Francesco
Abstract: Antiphospholipid antibody syndrome (APS) is a systemic autoimmune disorder characterized by venous and arterial thromboembolic (TE) disease, and/or pregnancy morbidity, associated with persistent elevated antiphospholipid antibodies (lupus anticoagulant, LA, anticardiolipin, aCL, and anti-beta2-glycoprotein I, anti-β2GPI). A 51 year-old man, smoker, presented to our ER with chest pain. EKG showed Q waves and STE in the anterior leads, with increased troponin levels. A diagnosis of anterior STEMI was made and he was taken into our catheterization laboratory, where a high burden thrombotic plaque determining LM and ostial LAD subocclusion was treated with PPCI and a DES implantation; in addition, multiple failed PCI attempts were performed on a distal LAD occlusion, and an integrilin bolus was administered. The patient was admitted to our CICU and a DAPT with ASA and Ticagrelor was started. TTE showed LVEF 40%, apical akinesis, septal and anterior hypokinesis, and no significant valve disease. An aPTT abnormal value (100.5 s; reference range 25–38.5 s) was detected, not corrected by aPTT mixing study. Given suspected autoimmune prothrombotic state, normal Hb and PLT values and low bleeding risk, LMWH 100 IU/kg every 12 h was started, in addition to DAPT with switch from Ticagrelor to Clopidogrel. LA and aCL and anti-β2GPI IgG were positive, with negativity of others rheumatologic tests, confirming primary APS diagnosis. Repeat TTE showed EF 50%. The patient was discharged in 'triple therapy' (DAPT plus LMWH), and referred to the rheumatology clinic. LA, aCL, and anti-β2GPI tests 12 weeks later were positive, confirming a triple positive APS and satisfying revised Sapporo criteria. The rheumatologist switched therapy to Clopidogrel plus Warfarin. At 3 months follow-up, the patient, former smoker, was asymptomatic and TTE confirmed EF 50%, so he was recommended to continue with his medical therapy. APS is rarely associated with AMI (∼5.5%) and in only 2.8% cases AMI represents the onset of the disease. AMI pathogenesis in APS is considered to be acute thrombosis of coronary arteries, in contrast with atherosclerotic plaque rupture in typical AMI. Key discriminators to identify APS as potential underlying cause of AMI include young age, previous unprovoked thromboses, low platelets count (they are consumed in the thrombotic process), high aPTT value (LA may interfere with assembly of the prothrombinase complex on phospholipids), coronary artery thromboses in the setting of otherwise normal otherwise appearing coronary arteries. APS antibodies have also pro-inflammatory activity on vascular endothelial cells, leading to accelerated atherosclerosis. aGAPSS score (high risk ≥10) is useful for risk stratification of recurrent thrombosis and AMI in young patients with APS. The treatment of AMI in APS is therefore a clinical challenge. Strict management of additional CV risk factors is crucial. VKA (INR >3 with Warfarin, INR2–3 with Warfarin and ASA) should be provided for life, because of the very high risk of recurrent TE. DOACs are less effective and less safe than VKAs for TE prevention in APS. The role of coronary stents, considering higher rates of stent thrombosis after PCI in APS patients triple therapy concomitant risks, requires further studies. Due to lack of large, randomized, prospective studies, there is no clear experts consensus about optimal antithrombotic therapy in secondary prevention after arterial TE. APS patients with STEMI should undergo PCI, usually associated with thrombus aspiration, and in selected cases DES implantation in culprit lesion followed by triple antithrombotic therapy with short-term DAPT and long-term VKA.